Study on Integration Mode of Station-level Weak Current System in Urban Rail Transit - SU Liyong; SHEN Zhanghong; YOU Yi; LI Minggan; GUO Song (Chengshi guidao jiaotong yanjiu, 2024)
Objective Restricted by operation and maintenance management modes, the traditional station-level weak current systems generally adopt a separate computer room mode, causing a certain waste of civil construction scale. Therefore, it is necessary to study the integration mode for weak current system at station-level in urban rail transit. Method Based on the current integration status of urban rail transit station-level weak current systems and combined with the project on Beijing Rail Transit Line 22, research and analysis are conducted on the computer room space and resource integration of station-level weak current systems. Result & Conclusion After system analysis, resource integration of some equipment in the station-level weak current systems (such as communication system, integrated monitoring system, automatic ticket vending and checking system, access control system and signal system) to the cloud is realized, which can comprehensively save about 3 m to 5 m of station space, and 250 000 to 300 000 yuan equipment construction investment. At the same time, the resource integration achieves the goal of reducing building space and gas extinguishing rooms, optimizing the pipe networks and so on.